Isoflurane Induced Malignant Hyperthermia in a Patient with Glucose 6-Phosphate Dehydrogenase Deficiency and Growth Hormone Abuse - Hojatolah Ravaei; Mohammad Javad Yavari Barhaghtalab; Vahid Salehi; Hossein Hejr (Case Reports in Anesthesiology)
Malignant hyperthermia is a pharmacogenetic disorder in the regulation of calcium in skeletal muscles which is related to an uninhibited muscle hypermetabolic reaction to potent inhalation agents, the depolarizing muscle relaxant succinylcholine, and to stressors such as vigorous exercise and heat. MH is diagnosed by the clinical presentation of the disease and laboratory testing. There are a few previous studies working on if there is an association between the occurrence of malignant hyperthermia and the existence of glucose 6-phosphate dehydrogenase (G6PD) deficiency, and there was no report on growth hormone doping in the literature. So, our main goal was to show this rare case of malignant hyperthermia seen in a G6PD patient with growth hormone abuse who underwent surgery and to find if there is an association between G6PD deficiency, growth hormone abuse, and malignant hyperthermia. Our patient was a 17-year-old boy with right lower quadrant abdominal pain and tenderness who underwent appendectomy. At the end of the operation, the patient developed with an increased heart rate (sinus tachycardia), increased body temperature and end-tidal carbon dioxide (ETCO2) level, masseter muscle rigidity, and then, generalized body rigidity, so the malignant hyperthermia susceptibility was considered. The patient was managed by cooling down the patient and the administration of dantrolene. We could hypothesize that malignant hyperthermia might be associated with G6PD deficiency as a triggering factor, but has no association with recombinant human growth hormone (rhGH) abuse. Another main lesson which this study tells us is to make a careful and proper history taking before going on an operation for preoperative evaluation and identification of patients with any form of suspicious drug abuse in order not to receive volatile inhalational agents and, also, performing some preventive measures including avoidance of heat extremes and restricting athletic activity in a patient with a history of malignant hyperthermia, and if the malignant hyperthermia susceptibility is suspected, urgent management should be carried out. As the association between G6PD deficiency, human growth hormone abuse, and malignant hyperthermia has remained unclear up-to-date, further potent studies are seriously needed in the future.